PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN PELANGGAN PT. DISTRIVERSA BUANA Studi Kasus pada pemakai Balsem cap Macan di Jakarta - Melyani Melyani (Universitas Bina Sarana Informatika, 2016)
The objective of the research is to know the effect of the product quality and service tocustomer satisfaction. This study was carried out at Jakarta Greater Area with 100respondents. Which were taken by propotional random sampling. The respondents werepeople who was user of Tiger Balm and live at Jakarta greater area.Data anlysis techniquesare used to test the hypothesis is correlation and multiple regression were oprated bycomputer using Statistical Product & Service Solution (SPSS). Computational results fortesting the model showed analysis of determination, and anlysis non parametrik regression.The results show the quality of product and service is a significant positive effect andcorrelation between quality product and service on customer satisfaction. The better thequality of the product it will be a positive impact on customer satisfaction. High-quality ofservices are services that can exceed the expectations of the consumer, the better the servicereceived by the customer it will be a positive impact on customer satisfaction.